16.0k views
15 votes
Solve the following equation. Explain the steps you used to solve.

6x−2=−3x+7

2 Answers

12 votes

Answer:

x=1

Explanation:

User Saramgsilva
by
5.3k points
13 votes

Answer:

X=1, i'm not sure if it's correct i didn't check it, okay i just plugged it in, x is = to 1

Step-by-step explanation: First you have to get the variable to one side of the equation by using the inverse operation of subtraction which is addition and add -3x to 6x making it 9x, then from there continue to use inverse operations.

User Ytpm
by
4.4k points